Effect of the Ba/Sr ratio on the optical properties of phosphate laser glass - Popov, A.S.; Uklein, A.V.; Zaderko, A.N.; Kozhanov, V.A.; Lisnyak, V.V.; Gayvoronsky, V.Ya. (Functional Materials, 2016)
Nonlinear optical (NLO) approach was utilized for the laser phosphate glasses characterization, being prepared by the molar substitution of Ba2 for Sr⁰²⁺ at a fixed ratio of other components in a mixture of Ba₁₋-x₀/Srx₀-P₂O₅-Al₂O₃-B₂O₃-RE₂O₃ (RE : Nd, La). The optical characterization of the glasses was provided by optical and FTIR spectroscopy and elastic scattering indicatrices analyses. It was shown that an efficiency of the photoinduced absorption/bleaching depends on the substitution Ba²⁺-Sr²⁺ level x due to the self-action of pulsed and CW laser radiation at wavelength 1064 nm. The proposed technique can be applied for the oxygen stoichiometry diagnostics for laser phosphate glasses. For the x = 0.25 composition it was obtained UV-vis range absorption and elastic scattering reduction within the lowest efficiencies of the NLO absorptive response under pulsed and CW laser excitation at wavelength 1064 nm. Such optical properties improvement was achieved by both the substitution level choice modification and the purification of the initial reagents.